Zinc Supplementation Effect on the Bronchial Cilia Length, the Number of Cilia, and the Number of Intact Bronchial Cell in Zinc Deficiency Rats - Andy Darma; Alpha Fardah Athiyyah; Reza Gunadi Ranuh; Wiweka Merbawani; Retno Asih Setyoningrum; Boerhan Hidajat; Siti Nurul Hidayati; Anang Endaryanto; Subijanto Marto Sudarmo (The Indonesian Biomedical Journal, 2020)
BACKGROUND: Airway epithelium is the first line of defense against a variety of exposures. Inflammatory processes, hyperresponsiveness and zinc deficiency cause epithelial damage. Zinc is involved in apoptosis and microtubule formation. However, its role in the integrity of bronchial mucosa and cilia is unclear.METHODS: To assess the effect of zinc on the integrity of the bronchial epithelium, 24 male Rattus norvegicus strain Wistar rats were randomized into four experimental groups: normal zinc diet group without zinc supplementation, normal zinc diet group with 60 ppm zinc supplementation, zinc deficient diet group without zinc supplementation, and zinc deficient diet group with 120 ppm zinc supplementation. Bronchial mucosal integrity was measured with the number of epithelial cells, and the number and length of cilia.RESULTS: Number of cell in normal zinc diet group was 8.8±1.82, while it was only 8.1±1.08 in zinc deficient diet group (p<0.001). Number of cilia per cell was 4.6±1.08 in normal zinc diet group, compared to 4.0±0.79 in zinc deficient diet group (p<0.001). Ciliary length also differ by 7.68±0.66 μm in normal zinc diet group and only 5.16±0.91 μm in zinc deficient diet group (p<0.001).CONCLUSION: Zinc supplementation of the normal zinc diet group affected the length of bronchial cilia. Zinc supplementation of the zinc deficient diet group affected the integrity of the bronchial epithelium, which was shown by the number and length of cilia, and the number of epithelial cells.KEYWORDS: zinc, bronchial epithelial integrity, cilia length, number of cilia, epithelial cell